Investigating the Nexus between Islamic Work Ethics and Organization Citizenship Behavior - Mushtaq, Ayesha; Nisar, Tahira; Ali, Hafiz Fawad (International Review of Management and Marketing, 2020)
The basic purpose of this research is planned to measure the Islamic Work Ethics (IWE) level and level of Organization Citizenship Behavior (OCB) in workers of banks of Lahore. It additionally investigated relationship between level of IWE and OCB. This study used the sample of three hundred employees from the banks of Lahore. For information gathering, the questionnaire was adopted, and results of the research demonstrated the level of IWE in Islamic bank's workers is high than other banks such as conventional, private and government banks. OCB level among Islamic bank's workers is high than the private, conventional and government bank. The results likewise demonstrated that the relationship between OCB and IWE is significantly positive. This research may improve the understanding of the people, employees and managers of banks about the understanding of the relationship between level of IWE and OCB. Keywords: Organization Citizenship Behavior, Islamic Work Ethics, Islamic Bank JEL Classifications: M19 DOI: https://doi.org/10.32479/irmm.9844